PENGARUH MODEL PEMBELAJARAN TIPE MAKE A MATCH BERBANTUAN MEDIA EXPLOSION BOX TERHADAP HASIL BELAJAR IPAS SISWA KELAS IV SD NEGERI 2 LAMCOT ACEH BESAR - Izzatul Jannah; Mislinawati; Suci Fitriani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The science learning outcomes of fourth-grade students at SD Negeri 2 Lamcot are still suboptimal due to teacher-centered learning and limited use of models and media that promote student engagement in the learning process. This study aimed to examine the effect of the Make a Match learning model assisted by Explosion Box media on students’ science learning outcomes on local wisdom topics. The study employed a quantitative approach with a quasi-experimental design using a nonequivalent control group. The subjects consisted of 44 students divided into an experimental class and a control class. The instruments used were pretest and posttest, and the data were analyzed using an Independent Sample t-test through SPSS version 25. The results showed that the average pretest scores of the experimental and control classes were 46.82 and 38.86, respectively. After implementing the Make a Match model assisted by Explosion Box media, the average posttest score of the experimental class increased to 86.36, while the control class reached only 71.14. Analysis indicated that this difference was significant (p = 0.00 < 0.05). Thus, the Make a Match model assisted by Explosion Box media has a significant effect on the science learning outcomes of fourth-grade students at SD Negeri 2 Lamcot